Simultaneous two-dimensional measurement of fuel–air ratio and temperature in a direct-injection spark-ignition engine using a new tracer-pair laser-induced fluorescence technique. (January 2016) - Lind, Susanne; Zigan, Lars; Trost, Johannes; Leipertz, Alfred; Will, Stefan
A planar tracer laser–induced fluorescence technique using a new tracer pair is introduced and has been utilized for the simultaneous detection of the fuel–air ratio and the temperature to characterize mixture formation inside a direct-injection spark-ignition engine. The new tracer pair consists of triethylamine and 3-pentanone, which are simultaneously added to the surrogate fuel isooctane. Triethylamine was used for the determination of the fuel–air ratio. The temperature distribution was evaluated with the two-line excitation laser-induced fluorescence technique using 3-pentanone. Prior to the internal combustion engine measurements, the tracer mixture was first investigated in a flow cell to demonstrate the spectral separability of the fluorescence signals and for the extension of the calibration data basis. As a first application, the tracer pair was applied inside a direct-injection spark-ignition engine operated with a split-injection scheme. For the late second injection, the fuel and temperature stratification was studied during the compression stroke. The measured temperature drop due to evaporative cooling effects was found to be about 100 K in the averaged data and up to 125 K in the single-shot measurements. The relation between fuel-rich areas and strong temperature drop can clearly be seen in the results. Furthermore, the suitability of the tracer pair to resolve cyclic variations is visualized.